...ohne Maaß veränderlich' : Novalis, women and writing - Hodkinson, James Richard (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2003)
This thesis re-examines the treatment of the feminine and of the female literary subject in the works of Hardenberg/Novalis. It contends that, whilst Hardenberg did not approach these themes in a manner wholly revolutionary for his time, his writing did begin to display a more evolving sense of feminine identity and to afford more communicative and creative potential to female subjects than has hitherto been suggested by critics.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin